2005
DOI: 10.1519/14313.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Practices of National Collegiate Athletic Association Division I Football Players

Abstract: The objective of this study is to evaluate the dietary practices of 28 football athletes on a National Collegiate Athletic Association (NCAA) Division I team using 3-day diet records. Student athletes completed 3-day diet records at 2 individual points of time, when no training table was available. Diet records were evaluated and were compared with the Third National Health and Nutrition Survey (NHANES III) data for the same ages and gender group. No differences in dietary practices of collegiate football athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…In the absence of MetSyn, the traditional recommendation would be to place these athletes on a fairly highcarbohydrate training diet and to provide enough protein for the increase in muscle mass stimulated by the training routine. 28 As was the case in the study of Cole et al, 29 many of our athletes seemed to value meat in the diet, as indicated by the high preference for meat on the Nutrition Attitude Survey. The negative correlations of meat preference with waist circumference, decreased body fatness, and apparent better glucose handling (eg, FBG and HgbA1c levels) deserve more attention from the research community amid the feuds over high-protein diets in athletes.…”
Section: Discussionmentioning
confidence: 65%
“…In the absence of MetSyn, the traditional recommendation would be to place these athletes on a fairly highcarbohydrate training diet and to provide enough protein for the increase in muscle mass stimulated by the training routine. 28 As was the case in the study of Cole et al, 29 many of our athletes seemed to value meat in the diet, as indicated by the high preference for meat on the Nutrition Attitude Survey. The negative correlations of meat preference with waist circumference, decreased body fatness, and apparent better glucose handling (eg, FBG and HgbA1c levels) deserve more attention from the research community amid the feuds over high-protein diets in athletes.…”
Section: Discussionmentioning
confidence: 65%
“…The energy and macronutrient intakes of our participants were generally higher than those of other research groups [8, 13], though a direct comparison is difficult due to variables such as the time of testing (e.g. off season, pre-season, post-season), their playing positions, and year of eligibility (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…Irrespective of the competition level and type of sport prolonged energy deficit may lead to decreased performance and health, including iron deficiency anemia and immunosuppression [5]. Special consideration should also be noted for adolescent athletes, as adequate energy intake is essential to maintain a number of factors such as growth, health, body mass and maturation [6].…”
Section: Introductionmentioning
confidence: 99%